Gastrointestinal Helminths of Magpies (Pica pica), Rooks (Corvus frugilegus) and Carrion Crows (Corvus corone) in Mazandaran Province, North of Iran - A Halajian; A Eslami; I Mobedi; O Amin; J Mariaux; J Mansoori; S Tavakol (Iranian Journal of Parasitology, 2011)
Background: Corvidae is a cosmopolitan family of oscine birds including crows, rooks, magpies, jays, chough, and ravens. These birds are migratory species, especially in the shortage of foods, so they can act like vectors for a wide range of microorganisms. They live generally in temperate climates and in a very close contact with human residential areas as well as poultry farms. There is no available information in the literature concerning the parasitic infections of these three species of corvidae in Mazandaran Province, northern Iran, so this study was conducted to clarify this.